Entre o tronco e o monte: convergências e divergências nas espiritualidades dos Indígenas Potiguara e do Carmelo Monástico da Paraíba - Mendonça, Joselma Bianca Silva de souza (2014)
The research in focus presents the dimensions Potiguara’s Indians spirituality and the Discalced Carmelitas of Paraiba, from the study of beliefs and rites in the San Francisco Village, located in the city of Baia da Traição PB and on the people’s testimonies who lived within a monastery. The first experience is of an ethnic group, remnant of people which saves axioms from the ancestors cultivated by the memory of the old trunk, considered sacred within tradition; the second experience, a religious order that search around a statute, a foundation to promote spirituality, in view of asceticism practices, contemplation and solitude of the cloister. Notes, presented in these two worlds, distinct ways to relate with the divinity. For both, we adopted the method of qualitative research, ethnography for the rituals, the rooted, the corners and the devotion of those realities. To justify the search, we use some theorists, such as: Barcellos (2012), Birth (2012), Eliade (2007), Otto (2011), Campbell (1990), Vilhena (2005), Palitot (2002), Vieira (2012), among other additional works here not mentioned. On Carmelita spirituality, we base in Cross (1996), Jesus (2003), Mesters (2001) and Albuquerque (2001). We conducted field research through journaling, participant observation and semi-structured interviews. Strategies and instruments of research which allowed us to be present in daily life, in celebrations acts and festivities which involve both of Potiguara Indians as well as the Carmelitas nun, seeking in its essence, understand the ways of spirituality manifestation. The Indians build a line of argument to keep alive their culture. The beliefs in the spirit of the ancestors as well as other entities have spiritual meaning of value within the tradition. Spirituality permeates the trajectory of these worlds, is in common elements of tradition, and is in devotions to the Catholics saints around darkness, promises, offices and the Rosary, as happens in Carmel. It is common to see the Potiguara Indians, same ethnic group, enriched by so many practices and devotions in spirituality. It is also a fact; realize with the Carmelite nuns, a doctrine founded on Christianity that is not surrendered to the standards imposed by modernity, while remaining faithful to a Rule for more than a thousand years. The way in which we conducted the research was ethnographic. For five years we were present in almost all the rituals of the indigenous peoples as well as the monastery. What follows in the work, is the result of such search and the need to be on-the-spot and be able to record the experience that emanates from the being, so vehement in Potiguara Indians and the Discalced Carmelites.